2013
DOI: 10.1080/10298436.2013.839791
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the emerging warm mix asphalt technology

Abstract: The asphalt industry is constantly attempting to reduce its emissions as concerns are growing on global warming. This is done by decreasing the mixing and compaction temperatures of asphalt mixtures without affecting the properties of the mix which is possible through numerous available technologies in the industry. The production of asphalt mix is done by warm mix asphalt (WMA) technology at considerably lower temperatures (120°C or lower). Less energy consumption, lower mixing and compaction temperatures, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(67 citation statements)
references
References 48 publications
0
59
0
Order By: Relevance
“…The use of WMA can lead to environmental benefits (reduced energy consumption, gas and fume emissions) as well as to economic/operational advantages such as lower production costs, longer hauling distances and extended construction periods (D'Angelo et al 2008;Capitao et al 2012;Rubio et al 2012;Kheradmand et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The use of WMA can lead to environmental benefits (reduced energy consumption, gas and fume emissions) as well as to economic/operational advantages such as lower production costs, longer hauling distances and extended construction periods (D'Angelo et al 2008;Capitao et al 2012;Rubio et al 2012;Kheradmand et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…By using these two additives, the manufacturing temperature of HMA is decreased by approximately 15 °C to 30 °C. A detailed description of these additives can be found in Kheradmand et al (2014). Based on permanent deformation tests under cyclic load, Ouni et al (2014) report that WMA mixtures manufactured with Cecabase ® generated resistances comparable to dense-type and HMA.…”
Section: Similar To Sasobitmentioning
confidence: 99%
“…This product, developed by Sasol Wax, is a synthetic wax produced in the coal gasification process (Hurley and Prowell, 2006d;Chowdhury and Button 2008;Ghandi et al 2010) and is generally added in a 3 % to 4 % proportion with respect to the total asphalt weight. This additive, when introduced to the asphalt, chemically changes the temperature-viscosity curve, generating a reduction in the manufacturing temperature of approximately 18 °C to 54 °C, and a 20 % reduction in the energy consumption of the asphalt plant (Kheradmand et al 2014). According to Nazzal et al (2011), when WMA mixtures are manufactured with Sasobit, the polluting emissions into the atmosphere decrease by at least 50 % for volatile organic compounds, 60 % for carbon monoxide, 20 % for nitrogen oxides, and 83 % for sulfur dioxide in comparison to HMA mixtures.…”
Section: Modification Of the Asphalt Or Asphalt Mixture With Additivesmentioning
confidence: 99%
“…erefore, WMA has been popularly used worldwide in a variety of applications [1][2][3]. However, studies conducted at the National Center for Asphalt Technology (NCAT) indicated that as the mixing temperatures are reduced for WMA, the mixtures show increased tendencies toward rutting and moisture susceptibility [4][5][6].…”
Section: Introductionmentioning
confidence: 99%